2022
DOI: 10.1186/s13102-022-00453-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between bio-motor ability, endocrine markers and hand-specific anthropometrics in elite female futsal players: a pilot study

Abstract: Background The second-to-fourth digit ratio (2D:4D) has been calculated for individual athletes and sports, but it has not been investigated in futsal performance. Therefore, the aim of this study was to investigate any relationships between 2D:4D of the dominant and non-dominant hands and physical capacity performances, selected functional variables and hormone concentrations in elite female futsal players. Methods Twenty-four elite female futsal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Tatar et al, found in their study that there is a connection between FFPI and finger length. In line with these studies, we think that looking at finger length ratio will provide information about personality and profession [ 20 , 39 , 39 , 43 , 44 , 44 ]. In the light of the studies, we reached out to individuals in different professional groups and investigated whether or not their finger length ratios were correlated with FFPI and CAAS test results.…”
Section: Introductionmentioning
confidence: 78%
“…Tatar et al, found in their study that there is a connection between FFPI and finger length. In line with these studies, we think that looking at finger length ratio will provide information about personality and profession [ 20 , 39 , 39 , 43 , 44 , 44 ]. In the light of the studies, we reached out to individuals in different professional groups and investigated whether or not their finger length ratios were correlated with FFPI and CAAS test results.…”
Section: Introductionmentioning
confidence: 78%
“…A football player or futsal athlete has to be fast while running, changing direction, attacking and defending throughout the match. Power is an important element, especially in sports that require speed and explosiveness (Farhani et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Futsal is a team sport that includes intermittent and high-intensity physical activities played with unlimited substitutions in a narrow 20x40m field. The fact that the futsal ball has a less bouncing feature forces futsal players to improve their ability to play faster by keeping the ball in play all the time (Farhani et al, 2022). This situation requires players to have the ability to make quick decisions under pressure in attack and defense, to be more mobile and faster, and to change direction suddenly (Dogramaci et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone, on the other hand, is important for muscle growth and recovery and its level monitoring can help pinpoint any imbalances that may affect readiness and performance. 55,56 Specifically, testosterone concentration (and some other sex hormones) is one of the primary determinant of sex-based differences in athletic and sports performance. 57 Therefore, hormone tests, especially those related to the menstrual cycle, are also critical for female players, specifically, tracking hormones such as estrogen and progesterone helps understand the potential impact of menstrual cycle on performance and recovery (although more high-quality evidence is needed to show what affect performance parameters).…”
Section: Other Objective Parametersmentioning
confidence: 99%